Diagnóstico de las conductas y actitudes violentas en niños/as, familias y profesores/as de dos escuelas de las zonas urbana y rural del cantón Azogues - Cadme Galabay, Rosa Victoria (2014)
The theme of the research focuses on the diagnosis of violent behaviors and attitudes of children aged between six and eight years old in two schools in urban and rural areas of Canton Azogues that affect family life , education and community and exercise of rights development and protection in the period 2012-2013. Issue that has been considered from the positive, where the first thing is to know the most relevant behavior and violent attitudes expressed by children , parents and teachers / as, second and third evaluation strategies have to be designed to reduce the violent behaviors and attitudes of group intervention, considering the basis of institutional Coexistence codes that have educational institutions at the Ministry of Education. It also involves the analysis of various conceptualizations for understanding of the research topic , providing analytical theories , concepts and results to the instruments applied in the target population. So it is important that all stakeholders , especially teachers / as have useful tools that allow you to know the reality and use strategies to explain and guide them to parents , community leaders and children on violence and school , family and community abuse, for adults not transmit their experiences of violence or abuse and violent behavior , not afraid to admit living or denounce violence , protect their children at all times, not silent because there is a law that defends the rights of children / as to not make the children victims of adult problems in different areas of daily life .